Dynamics of a multi-strain malaria model with diffusion in a periodic environment. Issue 1 (31st December 2022) - Shi, Yangyang; Zhao, Hongyong; Zhang, Xuebing
Abstract : This paper mainly explores the complex impacts of spatial heterogeneity, vector-bias effect, multiple strains, temperature-dependent extrinsic incubation period (EIP) and seasonality on malaria transmission. We propose a multi-strain malaria transmission model with diffusion and periodic delays and define the reproduction numbers R i and R ^ i ( i  = 1, 2). Quantitative analysis indicates that the disease-free ω -periodic solution is globally attractive when R i < 1, while if R i > 1 > R j ( i ≠ j, i, j = 1, 2 ), then strain i persists and strain j dies out. More interestingly, when R 1 and R 2 are greater than 1, the competitive exclusion of the two strains also occurs. Additionally, in a heterogeneous environment, the coexistence conditions of the two strains are R ^ 1 > 1 and R ^ 2 > 1 . Numerical simulations verify the analytical results and reveal that ignoring vector-bias effect or seasonality when studying malaria transmission will underestimate the risk of disease transmission.